Silencio - Scorsese, Martin, 1942-; Driver, Adam; Neeson, Liam, 1952-; Garfield, Andrew; Speak Up (DVD (Speak Up), 2016)
In the 17th century, two Portuguese Jesuit priests travel to Japan in an attempt to locate their mentor, who is rumored to have committed apostasy, and to propagate Catholicism.